2018
DOI: 10.1186/s41232-018-0069-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of IL-34 in an inflammatory cyst of the submandibular gland: a case report

Abstract: BackgroundCysts of the salivary glands are common lesions that occur in the context of various etiologies. Although the diagnostic importance of cysts in salivary gland diseases has been well studied, molecular mechanisms that control the related pathological process remain largely unknown. IL-34 is a novel cytokine that was discovered recently as a tissue-specific ligand of colony stimulating factor-1 receptor. Since its discovery, accumulating evidence has revealed emerging roles of IL-34 in various patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…The association of IL-34 staining in colorectal cancer tissues with patients' characteristics is summarized in Table 1. Together, these data indicate that colorectal cancers have the potential to express IL-34, consistent with previous reports [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: High Expression Of Il-34 Correlates With Poor Survival In Cosupporting
confidence: 92%
See 1 more Smart Citation
“…The association of IL-34 staining in colorectal cancer tissues with patients' characteristics is summarized in Table 1. Together, these data indicate that colorectal cancers have the potential to express IL-34, consistent with previous reports [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: High Expression Of Il-34 Correlates With Poor Survival In Cosupporting
confidence: 92%
“…In disease, IL-34 expression can be induced by various cells, where it plays pathological roles such as in autoimmune disease, inflammation, infection and metabolic disorders [7]. Accumulating evidence also suggests important roles for IL-34 in cancer, including tumor growth, angiogenesis, metastasis, immunosuppression, therapeutic resistance and pathological osteoclastogenesis [8][9][10][11][12][13][14][15][16][17][18][19]. In particular, IL-34 contributes to the induction of immunosuppressive tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Since NF‐κB is a master regulator of the inflammatory signaling pathway, IL‐34 is expected to be correlated with various inflammatory conditions. Consistent with this, an enhanced expression of IL‐34 has been reported in several pathological conditions accompanied by inflammation such as inflammatory bowel disease, coronary artery disease, chronic apical periodontitis, obesity, chronic liver disease in NAFLD, and lesions of the salivary glands . Importantly, IL‐34 was suggested to be involved in the pathological complications of these chronic conditions, such as renal dysfunction in chronic heart failure, liver fibrosis in NAFLD, and insulin resistance and T2DM in obesity …”
Section: Pathological Roles Of Il‐34supporting
confidence: 55%
“…Since IL‐34 is expressed at mRNA level in various tissues, this expression is expected to be changed under pathological conditions. Indeed, several studies have confirmed the enhancement of IL‐34 expression at mRNA and protein levels in the context of various diseases including autoimmune disorders, inflammation, infections, metabolic diseases, neurological disorders, and cancer . At the cellular level, IL‐34‐producing cells include synovial fibroblasts, immune cells, epithelial cells, endothelial cells, adipocytes, and cancer cells.…”
Section: Il‐34 Biologymentioning
confidence: 95%
See 1 more Smart Citation